Student Argumentation Structure in Solving Statistical Problems Based on Adversity Quotient - Aaidati, Iffanna Fitrotul; Subanji; Sulandra, I Made; Permadi, Hendro (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2022)
Evaluation of the argumentation structure is needed to check the quality of student argumentation to produce appropriate problem-solving. Such evaluation can be carried out by identifying the constituent components of the argument. This study aims to describe the structure of student argumentation in solving statistical problems based on the Adversity Quotient (AQ). This qualitative descriptive type of research involved 52 students who were taking statistical methods courses. Participants were classified into three Categories of Adversity Quotient based on the results of the ARP (Adversity Response Profile) questionnaire. Data were obtained using statistical problem tests and interviews. The results showed that students with the AQ Climber category were able to meet all the constituent components of argumentation when solving statistical problems. AQ Camper-type students are only able to meet three components, namely claims, evidence, and reasoning. Meanwhile, students with the AQ Quitter type are only able to fulfill one component, namely claims. Based on the results of the study, the level of Adversity Quotient determines the quality of the student's argumentation structure when solving statistical problems.DOI: https://doi.org/10.22342/jpm.16.2.16633.121-140